2x-5(x+3)=x(x-4)

Simple and best practice solution for 2x-5(x+3)=x(x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-5(x+3)=x(x-4) equation:



2x-5(x+3)=x(x-4)
We move all terms to the left:
2x-5(x+3)-(x(x-4))=0
We multiply parentheses
2x-5x-(x(x-4))-15=0
We calculate terms in parentheses: -(x(x-4)), so:
x(x-4)
We multiply parentheses
x^2-4x
Back to the equation:
-(x^2-4x)
We add all the numbers together, and all the variables
-3x-(x^2-4x)-15=0
We get rid of parentheses
-x^2-3x+4x-15=0
We add all the numbers together, and all the variables
-1x^2+x-15=0
a = -1; b = 1; c = -15;
Δ = b2-4ac
Δ = 12-4·(-1)·(-15)
Δ = -59
Delta is less than zero, so there is no solution for the equation

See similar equations:

| 71=23+v | | 30-3y=6 | | 3(2r-4)=r+3 | | 133=7c | | 133=c7 | | 39-3y=6 | | 83=2(3.14)r | | 2(b+40)=240 | | 525=(7x)(3x) | | 6(-2y-1)=-(13y+2) | | 5b+7(b-8)=-128 | | 3.60x+2.40(100-x)=312 | | 401.97=210+0.81x | | 5x+9=1+3x | | 4y+12=3y+4 | | -1(-x)=-1(10) | | 2/(9-7i)=0 | | (r,θ)=(5.8,5.8) | | 49+5(7g-3)=9(g-5) | | 3w^2+11w-42=0 | | 2/3(x+18)=8 | | (r,0)=(2.32,3.76) | | x^2=-2(3x+4) | | 5+2x=7x²-7 | | -10b-5-1=10+6b | | 2(h+5)=24 | | (2/15)x=4 | | -5+6r=9r+7 | | 4x-(60-x)=130 | | 2/15x=4 | | 1/2y+5=-18 | | -4k+6=-10 |

Equations solver categories